Optimal arrangement design of pipeline support by considering safety and production cost - In-Chang Yeo; Myung-Il Roh; Do-Hyun Chun; Seok Ho Jang; Jae Won Heo (International Journal of Naval Architecture and Ocean Engineering, 2023)
Ships are generally designed by modifying and improving base ships, and the design process includes designing the arrangement of pipeline layout and supports. The pipeline must be placed within a limited compartment because of the features of a ship with limited space. Therefore, the designer must arrange the pipeline by considering various factors, such as the connection between the equipment, efficiency, space utilization, and economic feasibility. Several stress analysis conditions must be satisfied to ensure the pipeline safety, and the arrangement of pipeline supports must be modified according to the stress analysis results.In this study, we proposed a method for optimizing the arrangement design of pipeline supports, considering safety and production costs. First, we set the type of pipeline support—whether to install the pipeline support on each node and whether to change the loop length as a design variable. In general, efficiently installing pipeline supports will improve safety and reduce production costs. Moreover, installing more pipeline supports than necessary limits the flexibility of the pipeline and reduces its safety. Therefore, safety and economy should be considered when installing pipeline supports. However, it is challenging to satisfy both conditions simultaneously with the conventional manual arrangement design methods for pipeline support. In this study, the pipeline support arrangement design process was formulated as an optimization problem to derive an optimal arrangement design. The objective function was set considering the safety and production cost, and the stress analysis conditions of the pipeline were set as constraints to ensure the safety of the derived arrangement design. By solving the formalized optimal arrangement design problem described above, an optimal arrangement design for pipeline support that meets the design purpose was derived. Finally, we verified the effectiveness of the proposed method by applying it to an actual pipeline. Consequently, it was confirmed that the optimal pipeline support arrangement design could be derived by considering both the safety and economic feasibility of the pipeline.